A Web-Based Information System for Student Affairs Letter Management : Design and Implementation in Padang State Polytechnics - Rasyidah Rasyidah; Meri Azmi; Widya Wicaksana (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2020)
Today, to create the official student affair letters in the Padang State Polytechnic has not been computerized yet, so students have to queue and it takes a long time. With this developed system, there is no longer a queuing process at the counter, students can fill out a form through the system and will receive a notification when the official letter has been confirmed from related section. With this system, the campus is also facilitated in the process of searching for data, for example knowing the student who made the letter, the graph of each category of making a letter per year from the letter application. The system is built with the PHP programming language with Code Igniter framework and MySQL as DBMS. Pembuatan surat kemahasiswaan yang dilakukan di Politkenik Negeri Padang belum terkomputerisasi, sehingga mahasiswa harus mengantri dan waktu yang dibutuhkan lama. Dengan sistem yang dikembangkan ini, tidak adalagi proses antrian di loket, mahasiswa dapat mengisi form surat melalui sistem dan akan menerima notifikasi ketika surat telah dikonfirmasi dari pihak terkait. Dengan sistem ini, pihak kampus juga dimudahkan dalam proses pencarian data, misal mengetahui mahasiswa yang melakukan pembuatan surat, grafik setiap kategori dari pembuatan surat pertahun dari permohonan surat. Sistem dibangun dengan bahasa pemrograan PHP dengan framework Code Igniter dan MySQL sebagai DBMS.